The effect of a single BRCA2 mutation on cancer in Iceland. Issue 7 (1st July 2002) - Tulinius, H; Olafsdottir, G H; Sigvaldason, H; Arason, A; Barkardottir, R B; Egilsson, V; Ogmundsdottir, H M; Tryggvadottir, L; Gudlaugsdottir, S; Eyfjord, J E
Abstract : Objective: To estimate the risk of malignant diseases in families of probands with the same mutation in the BRCA2 gene . Design: A cohort study using record linkage of a breast cancer family resource and the Icelandic Cancer Registry. Setting: Iceland. Subjects: Families of 995 breast cancer patients, from which 887 were tested for a single founder 999del5 mutation; 90 had the mutation and 797 did not. Results: Relatives of probands with the mutation had significantly increased relative risk (RR) of breast cancer. For first degree relatives, the RR was 7.55 (95% CI 6.04 to 9.03) but was 1.72 (95% CI 1.49 to 1.96) in first degree relatives of probands without the mutation. For prostate and ovarian cancer, the first and second degree relatives of probands with the mutation had a significantly increased RR, but in families of probands without the mutation no significant familial risk was found. Conclusions: The 999del5 mutation in the BRCA2 gene explains a substantial proportion of familial risk of breast cancer in Iceland, but significant familial risk remains in relatives of probands without the mutation. For prostate and ovarian cancer, the mutation accounts for most of the familiality observed in families of breast cancer patients.